Hubungan Self-Compassion Dengan Tingkat Stress Dalam Menghadapi Osce Pada Siswa-Siswi Keperawatan Kelas Akhir Di SMK Kesehatan Logos - Adinda Hanum; Marisca Agustina; Indri Sarwili (Pusat riset dan Inovasi Nasional, 2024)
OSCE is a form of test used as a formative and summative exam to assess skill competency in various health sciences. OSCE requires students to demonstrate clinical skills, medical knowledge, and communication skills in realistic simulated situations. This makes the stress level in adolescence higher based on one of the factors that can reduce stress and improve students' well-being is self-compassion. This research is a quantitative research with a correlational descriptive design with a cross sectional approach. Results: Low category Self-Compassion means the lower the Self-Compassion, the higher the stress level and respondents with Stress Levels are in the medium stress category. And in the severe stress category. And the Pvalue is .002, so there is a significant relationship between self-compassion and stress levels in final year nursing students at Logos Health Vocational School in 2023. Conclusion: There is a relationship between self-compassion and stress levels in facing the OSCE among final year nursing students in Logos Health Vocational School in 2023.